Cognitive emotion regulation and life satisfaction among students from Mainland China in Malaysian universities - Weidi, Zhou; JeeChing, Pang (Frontiers in Education, 2023)
This study investigated the relationship between cognitive emotion regulation and life satisfaction among mainland China students in Malaysian universities. It aimed to determine the level of life satisfaction, the frequency of using cognitive emotion regulation, the correlation between the two variables and the predictive factors of life satisfaction. Four hundred and ninety (490) participants were selected from twelve universities in Malaysia through random sampling, one hundred and ten (102) for pilot study, three hundred and eighty eight (388) for final study. A quantitative research design was developed to conduct the investigation using two questionnaires which are Multidimensional Students’ Life Satisfaction Scale (MSLSS) and Cognitive Emotion Regulation Questionnaire (CERQ). Data was analyzed using statistical tools SPSS 26 and Smart PLS (SEM) 3.0. Findings showed that a high proportion of 72.4% of the participants demonstrated a high level of life satisfaction of Mainland China students in Malaysian universities and 48.7% of Mainland China students always used cognitive emotion regulation. 12.6% Mainland China students displayed a low level of life satisfaction and 13.4% of them rarely used cognitive emotion regulation. In conclusion, there was a significant relationship between cognitive emotion regulation and life satisfaction of which positive reappraisal, positive refocusing, refocusing on planning of cognitive emotion regulation had significant predictive powers on life satisfaction for Mainland China students in Malaysian universities.